O sentido público da praia urbana - Pereira, Simone de Araujo (2016)
This these aims to understand the beach by the analysis and the practices established in the stretch-of-sand, as well as to analyze the ‘beach lifestyle”. The study was developed in the urban beaches of Natal city, capital of Rio Grande do Norte. The beaches Ponta Negra, Meio Beach, Areia Preta and Redinha comprise Natal coastline. The understanding of the public sense of urban beach, initially from the recognition of the sea bathing history and the process of bringing the city to the beach, has revealed two major aspects regarding the pattern of the urban beach: the desire for living by the sea, and the tensions between the mainland values and practices that emerged from the beach. The desire has been presented as beach configurator, as it is fulfilled by feedback expressions of infinite desires. Tensions, which are not necessarily the same, are still observable on the beach. It is said that there is always something new that can be done on the coast that seems to defy the mainland rules. The beach is perceived by its ephemerality (characterized by impermanence, as it has a not fixed dynamics), fluidity ( in different forms of appropriation), and fugacity ( its dynamics speed, for the flows which determine the logic of the cities). The beach, as part of the city, has become a leisure space and has emerged as the possibility of freedom from the exhaustive dynamics of the city. The beach lifestyle, comprising the cities, styles and people, is normally understood as casual, free and relaxed, when it is analyzed within the city area, it is recognized the resonance of urbanism in the determination established with the city, The notion of style is rewarded from the notion of design. Thus, the “beach lifestyle” is revealed as a redesign of the urban, and it has been observed that it is not so casual, not so free and not so relaxed.